PENGARUH KUALITAS PRODUK, CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KOPI PADA APLIKASI ONLINE DIMASA PANDEMI COVID-19 - Indra Ade Irawan (KELOLA: Jurnal Ilmiah Manajemen, 2021)
The purpose of this study was to determine and analyze the effect of product quality, brand image and price on Coffee Purchasing Decisions in Online Applications during the Covid-19 Pandemic. The population in this study is the community who use online applications in the area of Tangerang City Selatang (Grabfood, Gofood, and Shoppeefood). The sample used is 100 respondents. The sampling method uses Convinience Sampling. The data collection method used survey method, with the research instrument was a questionnaire. The data analysis method used was multiple linear regression analysis. The results of the research hypothesis testing indicate that the variable product quality has a positive and significant effect on the decision to buy coffee in online applications, brand image has a positive and significant effect on the coffee purchase decision in the online application, and the price has a positive and significant effect on the coffee purchase decision in the online application